2017
DOI: 10.1016/j.cortex.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct-current stimulation modulates offline visual oscillatory activity: A magnetoencephalography study

Abstract: Transcranial direct-current stimulation (tDCS) is a noninvasive neuromodulatory method that involves delivering low amplitude, direct current to specific regions of the brain. While a wealth of literature shows changes in behavior and cognition following tDCS administration, the underlying neuronal mechanisms remain largely unknown. Neuroimaging studies have generally used fMRI and shown only limited consensus to date, while the few electrophysiological studies have reported mostly null or counterintuitive fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 77 publications
3
17
0
Order By: Relevance
“…While we did not find a significant change in spontaneous alpha for the cathodal tDCS group in the present study, this previous work supports the notion that tDCS can lead to changes in spontaneous activity. Our two previous MEG studies using tDCS, which involved roughly 50% of the same participants, also showed the same net effect in that spontaneous alpha power was significantly elevated in the anodal tDCS group (Heinrichs‐Graham, McDermott, Mills, Coolidge, & Wilson, ; Wilson, McDermott, Mills, Coolidge, & Heinrichs‐Graham, ). It is possible that anodal tDCS of the occipital cortices results in an increase in spontaneous alpha activity, which ultimately broadly impairs visual attention processes and thereby performance on the flanker and similar tasks.…”
Section: Discussionsupporting
confidence: 59%
“…While we did not find a significant change in spontaneous alpha for the cathodal tDCS group in the present study, this previous work supports the notion that tDCS can lead to changes in spontaneous activity. Our two previous MEG studies using tDCS, which involved roughly 50% of the same participants, also showed the same net effect in that spontaneous alpha power was significantly elevated in the anodal tDCS group (Heinrichs‐Graham, McDermott, Mills, Coolidge, & Wilson, ; Wilson, McDermott, Mills, Coolidge, & Heinrichs‐Graham, ). It is possible that anodal tDCS of the occipital cortices results in an increase in spontaneous alpha activity, which ultimately broadly impairs visual attention processes and thereby performance on the flanker and similar tasks.…”
Section: Discussionsupporting
confidence: 59%
“…To control for Type 1 error, the two‐stage procedure described above (Section 2.5) was employed, with the criteria of at least 10,000 permutations and a threshold of p < .05. Of note, a similar analytical approach has been adopted in previous MEG studies of oscillatory activity (Grent‐'t‐Jong, Oostenveld, Jensen, Medendorp, & Praamstra, ; Heinrichs‐Graham, Hoburg, & Wilson, ; Heinrichs‐Graham, Kurz, Gehringer, & Wilson, ; Heinrichs‐Graham, McDermott, Mills, Coolidge, & Wilson, ; McDermott, Wiesman, Proskovec, Heinrichs‐Graham, & Wilson, ; Muthukumaraswamy et al, ). Additionally, to ensure that transient evoked responses did not contribute to conditional differences, we conducted the same virtual sensor time series analyses while subtracting out evoked activity.…”
Section: Methodsmentioning
confidence: 99%
“…activity(Grent-'t-Jong, Oostenveld, Jensen, Medendorp, & Praamstra, 2013Heinrichs-Graham, Hoburg, & Wilson, 2018;Heinrichs- Graham, Kurz, Gehringer, & Wilson, 2017a;Heinrichs-Graham, McDermott, Mills, Coolidge, & Wilson, 2017b;McDermott, Wiesman, Proskovec, Heinrichs-Graham, & Wilson, 2017; …”
mentioning
confidence: 99%
“…With regard to the degree of focality, studies have shown that HD-tDCS directly over the motor cortex at intensities derived from current density modelling elicits MEPs, while such predicted stimulation intensities at sites just anterior and posterior of the motor cortex do not elicit MEPs (Edwards et al 2013). Importantly, tDCS has been found to modulate behavioural performance across a variety of cognitive domains, depending on the location of stimulation, and further it differentially influences the neural oscillations essential to these processes (Hanley et al 2016;Marshall et al 2016;Heinrichs-Graham et al 2017;Wiesman et al 2018;Wilson et al 2018;McDermott et al 2019).…”
Section: Introductionmentioning
confidence: 99%